1971
DOI: 10.1111/j.1365-2621.1971.tb06406.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Nonlogarithmic Survivor Curves of Heated Bacteria

Abstract: Complex survivor curves of heated bacteria are interpreted to be composites of several convex survivor cutves that represent populations of different heat resistances in a single culture of bacteria.The variation in heat resistance appears to be physiological rather than genetic since subcultures of heat-resistant cells were no more heat resistant than the parent culture. Composite cures can appear to be nearly exponential.Results support a multiple-site hypothesis of thermal death. Tailing of survivor curves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 18 publications
5
24
1
3
Order By: Relevance
“…Even though inactivation of cells within each clump would (1992) found that inactivation of E. coli by high pressure was logarithmic at 250 MPa for 20 min at 40°and 50°C. However, as has been widely documented in thermal and irradiation resistance studies (Moats 1971;Moats et al 1971; Silverman at below 30°C, a small proportion of survivors appeared to be less sensitive to pressure, resulting in a tailing effect. This and Sinskey 1977), inactivation by high pressure did not always follow simple first order kinetics (logarithmic death effect could be a result of the membranes of these cells undergoing a liquid crystalline to gel transition at ¼30°C.…”
Section: ------------------------------------------------------mentioning
confidence: 99%
See 2 more Smart Citations
“…Even though inactivation of cells within each clump would (1992) found that inactivation of E. coli by high pressure was logarithmic at 250 MPa for 20 min at 40°and 50°C. However, as has been widely documented in thermal and irradiation resistance studies (Moats 1971;Moats et al 1971; Silverman at below 30°C, a small proportion of survivors appeared to be less sensitive to pressure, resulting in a tailing effect. This and Sinskey 1977), inactivation by high pressure did not always follow simple first order kinetics (logarithmic death effect could be a result of the membranes of these cells undergoing a liquid crystalline to gel transition at ¼30°C.…”
Section: ------------------------------------------------------mentioning
confidence: 99%
“…These tended to be an initial rapid reduction in numbers followed by a gradual tailing off in the inactivation rate. Inactivation differences are illustrated by the D-values listed in Tables 2 Table 2 Decimal reduction time values* (D-values, min) for the ------------------------------------------------------temperature ----------------------------------------------------- ----------------------------------------------------- ----------------------------------------------------- --------------------------------------------------- ----------------------------------------------------- it undergoes an increase in hydration due partly to the elecobtained for inactivation of Lm1 and Lm3 in 8% (w/v) BSA trostriction of water molecules around newly exposed charged were 18·7 and 17·4 min, respectively, compared to 12·4 and groups (Masson 1992). It may be possible that once the 12·1 min for inactivation of these strains in 10% (w/v) denaturant (i.e.…”
Section: ------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed Pflug and Holcomb (1991) estimated that only one-third of thermal destruction data follow such kinetics. Deviations take the form of shoulders or tails, and this subject has been reviewed (Moats et al 1971;Cerf 1977). There are two basic explanations why first-order kinetics are not followed.…”
Section: Functions To Describe Thermal Inactivation Kinetics Of Bactementioning
confidence: 99%
“…Some are based on understanding the physiological mechanism of inactivation. For example, Moats et al (1971) assumed that targets are clumped at critical sites within the cell, Kormendy and Kormendy (1997) assumed that there is a distribution of resistance within the population, and Smerage and Teixeira (1993) assumed that heterogeneity occurs by adaptation to heat during heating. Other models involve empirical curve fitting (e.g.…”
Section: Functions To Describe Thermal Inactivation Kinetics Of Bactementioning
confidence: 99%